THD analysis and its mitigation using DSTATCOM integrated with EV charging station in the distribution network - Dhami, Kavita; Saggu, Tejinder Singh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
With the increase in carbon emissions, noise pollution and other environmental impacts caused by conventional vehicles, the demand for electric vehicles (EVs) is continuously increasing in the market. The transport sector has also been revolutionized with the use of EVs. The unique features such as reduction in noise pollution, carbon emissions and running costs and the capability of EVs to work in both grid-vehicle (G2V) and vehicle-grid (V2G) have made EVs popular nowadays. Still, it has several effects on the power distribution grid. There are several power issues due to the incorporation of electric vehicles (EVs) in the distribution network such as voltage instability, harmonics, and voltage fluctuations. This research paper focuses mainly on the harmonics caused in the system when EVs are connected to the distribution side. A distributed static compensator (DSTATCOM) based on the d-q theory is introduced to mitigate the harmonics along with the improvement in the voltage profile of the distribution side. By using MATLAB Simulink, the performance of DSTATCOM is validated and the comparison of the proposed approach is also done with that of similar work already existing in the literature.